1992
DOI: 10.1159/000168489
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of the Soluble lnterleukin-2 Receptor Are Dependent on the Kidney Function

Abstract: We have investigated the influence of kidney function on soluble interleukin-2 receptor (S-IL-2R) serum levels. S-IL-2R is a glycoprotein with a molecular weight of 45 kDa. The serum concentration of S-IL-2R was positively correlated to serum creatinine (r =0.35) and complement factor D (r = 0.30), a low molecular weight protein, and the reciprocal value of S-IL-2R was negatively correlated to 51Cr-EDTA clearance (r= -0.35). When measuring S-IL-2R and factor D in a wide range of serum creatinine (14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…However, unlike other previous results [29], the lower levels of this marker in the serum and urine of transplant infection cohort (compared with rejection and normal transplant groups) could be attributed to two reasons. The first reason could be the low number of patients in this group (n=3), and the second reason could be due to the normal renal transplant function [30]. The results of my study were different from that of Cassiraghi, et al [31] in many ways.…”
Section: Discussioncontrasting
confidence: 66%
“…However, unlike other previous results [29], the lower levels of this marker in the serum and urine of transplant infection cohort (compared with rejection and normal transplant groups) could be attributed to two reasons. The first reason could be the low number of patients in this group (n=3), and the second reason could be due to the normal renal transplant function [30]. The results of my study were different from that of Cassiraghi, et al [31] in many ways.…”
Section: Discussioncontrasting
confidence: 66%
“…This type of activation is initiated by interaction with an antigen, or a mitogen, such as seen in autoimmune and infectious diseases. On the other hand, it has been shown that a reduced kidney function could cause an accumulation of S-IL-2R (35). Our patients were carefully investigated, and we found nobody with kidney dysfunction.…”
Section: Discussionmentioning
confidence: 59%
“…Combined data suggest that sIL-2R levels may correlate with disease intensity in patients with iRPF. However, the observed association between baseline sIL-2R levels and sCr should be interpreted with caution as it may also reflect renal impairment, since sIL-2R is cleared by the kidneys [23]. Indeed, in patients with sarcoidosis, it has been suggested that elevated sIL-2R levels may not only reflect disease activity but also accumulation through impaired renal clearance [24].…”
Section: Discussionmentioning
confidence: 99%